If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + 7) + (11x + -2) = 90 Reorder the terms: (7 + 6x) + (11x + -2) = 90 Remove parenthesis around (7 + 6x) 7 + 6x + (11x + -2) = 90 Reorder the terms: 7 + 6x + (-2 + 11x) = 90 Remove parenthesis around (-2 + 11x) 7 + 6x + -2 + 11x = 90 Reorder the terms: 7 + -2 + 6x + 11x = 90 Combine like terms: 7 + -2 = 5 5 + 6x + 11x = 90 Combine like terms: 6x + 11x = 17x 5 + 17x = 90 Solving 5 + 17x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 17x = 90 + -5 Combine like terms: 5 + -5 = 0 0 + 17x = 90 + -5 17x = 90 + -5 Combine like terms: 90 + -5 = 85 17x = 85 Divide each side by '17'. x = 5 Simplifying x = 5
| 14-y=-5 | | 7x-14+8x=-134 | | 0.8x-2.9=2.3x+1.1 | | 12.7=.5(.125)v^2 | | -5+x+22=-1 | | 18x=4.5/1 | | X^2+24x+sqr(x^2+24x)=30 | | -3/5*1.25 | | 14x-15(56-x)+62x-16x=2085 | | 6z-85+2x+105=180 | | 9+m=3 | | 7x+19+11x-89=180 | | 1.25*(-3/5) | | x+1.19x=14000 | | 11x-65+29=180 | | 4x-3x=10+2 | | X+Y+Z=79 | | 4x^6+9x^3+2=0 | | .25x-7=1 | | kx^2-2x+2=0 | | 22x-9=x | | 8x-4x=7x-1 | | 9p+8p+6p-6= | | y-12= | | x+x*1.19=14000 | | 5x=1055 | | 2w+25=6w+1 | | 5x-7+8x-55=180 | | 4x+7=47+2x | | 1/4x-7=1 | | 7(x-4)+2=51 | | f(t)=-16t^2+104t+56 |